MANAGEMENT OF PULMONARY TUBERCULOSIS IN RELAPSE PATIENT - Syakti, Raihan Syafiin (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Morbidity, mortality, and disability of tuberculosis (TB) increases with the increasing life expectancy, the increasing number of smokers, and relapse of tuberculosis. Tuberculosis disease is an infectious disease that is directly caused by the Mycobacterium tuberculosis bacteria. Source of infection is the TB patients (with positif acid bacillus) that can spread the bacteria through the air into the respiratory droplets. The patient, 45 years old male, came to Rumah Sakit Umum Abdul Moeloek(RSAM), with chief complaint of coughing and shortness of breath accompanied with fever since a month ago. Shortness of breath continues throughout the day, this symptom was felt even worse if patient had a lot of activities. Fever was felt at any time since a week ago. This complaint is accompanied by productive yellow phlegm cough. Weight loss occured during the last 6 months. Patient had history of 6 months pulmonary tuberculosis treatment and smok ing for 10 years. Patient also had history of pleural fluid punction procedure in the chest. The patient had no history of diabetes, accidents, or heart disease. Relapse pulmonary tuberculosis should be diagnosed and treated as soon as possible to avoid complications such as acute respiratory distress. The management of relapse pulmonary tuberculosis is medication for 8 months and which divided by 2 stage, intensive stage and advanced stage. For advanced stage, if available, can be performed antibiotic resistant tests, the results can provide appropriate drug choice. [J. Agromed Unila 2014; 1(3):207-210] Keywords: drug resistant, pulmonary tuberculosis, relapse